2010
DOI: 10.1590/s0101-98802010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e perfil nutricional de pacientes com câncer colorretal colostomizados

Abstract: INTRODUÇÃOCâncer é o nome dado a um conjunto de mais de 100 doenças que têm em comum o crescimento desordenado (maligno) de células que invadem os tecidos e órgãos, podendo espalhar-se (metástase) para outras regiões do corpo. 1A incidência do câncer cresce no Brasil, como em todo o mundo, num ritmo que acompanha o envelhecimento populacional decorrente do aumento da expectativa de vida. É um resultado direto das grandes transformações globais das últimas décadas, que alteraram a situação de saúde dos povos pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 13 publications
1
11
0
7
Order By: Relevance
“…Studies analyzing people with malignant colorectal neoplasms show that 60 and 95% of people are married and live with a spouse, respectively 14 . The study also showed prevalence of Catholic and Evangelical patients among definitive and temporary colostomy patients, respectively, who reported increased faith after the disease diagnosis, with predominance in the group of definitive colostomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing people with malignant colorectal neoplasms show that 60 and 95% of people are married and live with a spouse, respectively 14 . The study also showed prevalence of Catholic and Evangelical patients among definitive and temporary colostomy patients, respectively, who reported increased faith after the disease diagnosis, with predominance in the group of definitive colostomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Only 41.2% of the participants reported practicing physical activity regularly. The practice of physical activity is not common in the population with stomas (26) . Although not the experience of this group, the Brazilian Association of People with Stoma guides the practice of exercises, using the innumerable benefits related to health as a whole, positively influencing self-esteem, mental capacity, cholesterol, depression, chronic diseases, among others.…”
Section: Resultsmentioning
confidence: 99%
“…The aspect of social relations was the most negatively emphasized [10,11]. In Poland, a survey involving 737 patients with ostomies (71%, 18%, 11% with a colostomy, ileostomy and urostomy, respectively) found a similar result regarding the negative impact on social life [12].…”
Section: Introductionmentioning
confidence: 82%